Automation in Developing Technical Documentation of Telecommunication Networks - Šarić, Slavko; Božanić, Zoran; Svalina, Romeo (Promet - Traffic&Transportation, 2004)
During the last decade of the 20th century, intensive developmentof telecommunication infrastructure set high requirementsregarding technical documentation that started to haveproblems in following the changes in the network. In the lastseveral years HT made a great shift regarding automation andpresentation of technical documentation, that is introductionof GIS (Geographic Information System), as precondition forthe introduction of DIS (Documentation Information System),thus realising the necessary preconditions to use the gatheredand organised spatial and atllibute data, for higher quality ofanalysis, processing and repair of interference in the telecommunicationnetwork The aim of this paper is to inform aboutthe segments and computer programs used for the developmentof technical documentation.